Socioeconomic and health aspects of quilombola populations in the state of Piauí, Brazil (Research, Society and Development, 2020)
Among the group of excluded individuals in Brazilian society, the most marginalized are still blacks. In this group, rural blacks are the most alienated from the new processes of social construction. The present study aimed to analyze health and socioeconomic aspects in quilombola communities in the state of Piauí. The research presents socioeconomic and health aspects in 15 communities in the State of Piauí. It is an exploratory, cross-sectional study of qualitative and quantitative nature, where the target population was 1,239 members in 15 quilombola communities identified in the State of Piauí. The average age was 30.1 years, with the age range between 0 and 89 years. Females were 55%, males 45% of the population. Illiterate were 20%, while 47.6% had not completed elementary school. Income of up to two minimum wages was 88.6%. Students 27.9% and rural worker 39.5% were the majority of the population. Of the houses, 74.1% had little or no sanitary condition. The use of medicinal plants occurred in 32.5%. The non-use of pesticides was reported by 96.8% of farmers. Inbreeding marriages were detected in 18.0% of the studied families. The research indicates the need for public policies focused on the characteristics and needs of these populations.